(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
This article discusses the significance of game-based methods in teaching English to preschool children. It analyzes how games influence children’s cognitive, emotional, and social development, and explains why playful learning increases motivation and language retention. The article also outlines effective types of games, their methodological principles, and practical recommendations for preschool educators. The results show that game-based learning creates a natural, stress-free environment in which children acquire English more easily and actively.